Extraction and characterization of gelatin from skipjack tuna (katsuwonus pelamis) bones - Peñera, Liane Rae Ivana R.
The objectives of this study were 1) to determine the optimum extraction temperature of skipjack tuna bone gelatin based on gel strength; 2) to analyze the gelatin extracted at optimum temperature for protein content, moisture content, ash content, melting temperature, pH, viscosity, color, and clarity; and 3) to compare the results with those of commercial gelatin. Phase I of the experiment entailed extraction of gelatin for 6 hours from pre-cooked tuna bones at three different temperatures (45°C, 55°C, and 70°C). For Phase II, commercial gelatin and skipjack gelatin were analyzed for physicochemical characteristics. The extraction temperature that yields skipjack tuna bone gelatin with the highest gel strength was determined to be 70°C. However, the mean gel strength value (10.77 g ± 6.2) was significantly lower (P < 0.05) than that of commercial gelatin (53.93 g ± 11.5). Skipjack gelatin was found to have significantly lower protein content (25.88% ± 12.46), ash content (0.53% ± 0.099), pH (3.73 ± 0.015), viscosity (0.9 ± 0.2 cP), and transmittance (%T = 20.4 ± 0.1) than commercial gelatin. The mean moisture content (14.07% ± 0.65) of skipjack bone gelatin did not have significant difference (P > 0.05) from that of commercial gelatin. Compared to commercial gelatin, skipjack gelatin is darker (L = 50.68 ± 0.01) and more orange in color (a = 9.09 ± 0.01, b = 54.37 ± 0.04). The results of the study suggest that skipjack tuna bone gelatin extracted at 70°C is not a good alternative to commercial gelatin in terms of physico-chemical properties.